Le post-humanisme chinois et la science-fiction politique de Chen Qiufan - Ron S. Judy (ReS Futurae)
One of the youngest of the major sf authors active in China today, Chen Qiufan is most often associated with cyberpunk, mainly because he is grounded in a critique of the near future and concerned with the ways in which biotechnology affects and alters our perception of the human body. This essay examines the “posthumanist” dimensions of three sf stories by Chen Qiufan (a.k.a. Stanley Chan) : “Smog Society” (2010), “Year of the Rat” (2009), and “The Flower of Shazui” (2012), with the aim of establishing whether there are any substantial differences between posthumanism in the Chinese and Euro-American cases. I tentatively conclude that there are differences and that the main one is that the Chinese variant is more directly “post-humanist” (i.e., affiliated with philosophical humanism) insofar as it remains deeply concerned with the Marxisthumanist idea of alienated agency.